Does debt affect profitability? An empirical study of French trade sector - Mazen Kebewar (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This article aims to expand existing empirical knowledge on the impact of debt level on profitability of companies. We analyze a sample of an unbalanced panel of 2325 unlisted French companies of trade sector spanning over a period of 1999 to 2006. By using the generalized method of moments (GMM), we show that the debt affects negatively the profitability, not only linearly, but also, in a non-linear (concave) way. However, while analyzing according to different size classes (VSEs, SMEs and LEs); we find that the linear negative effect becomes larger and the non-linear effect is significant only in small and medium-sized enterprises (SME).
Keywords: C33; G32; L25; 330; Debt; GMM; Panel data; Profitability